Justiça restaurativa : uma leitura e partir do viés ético - Tomasi, Geórgia Ramos (My University, 2021)
Restorative justice emerged in the 1970s as a new way of doing justice. It differs from punitive and distributive methods, whose predominant concern involves the violation of the norm. Restorative practices are thought of as processes in which the people affected by the offending act - victim, aggressor, family and/or community - seek, through their testimonies, to repair and satisfy the needs arising from the conflict situation. The general objective of the work is to discuss the ethical reflections about the restorative practices as a way to reach justice, and to search, through specific objectives, to present the main conceptions of justice and ethics; to understand the passage from the conception of retributive justice to the conception of restorative justice; to conceptualize the guiding concepts of restorative justice; to interpret ethically the principles and guiding objectives of the Municipal Restorative Peacemaking Program. This work aims to propose, through an exploratory qualitative bibliographic research, ethical reflections about restorative practices as a way to achieve justice. The exploratory design was chosen because its main objective is to present a panorama of the delimited field of research, in order to point out concepts, areas of action and points of interface of the researched theme. The exploratory research will allow the researcher to refine ideas and build hypotheses from the results obtained. It seems to be ideal so that the objective - to propose ethical reflections regarding restorative practices as a way to achieve justice - can be reached. [resumo fornecido pelo autor]
A justiça restaurativa surge na década de 1970 como uma nova forma de se fazer justiça. Diferencia-se dos métodos punitivos e distributivos, cuja preocupação predominante envolve a violação da norma. As práticas restaurativas são pensadas como processos em que as pessoas afetadas pelo ato infrator - vítima, agressor, familiares e/ou comunidade, - buscam, através dos seus testemunhos, reparar e satisfazer as necessidades advindas da situação de conflito. O objetivo geral do trabalho é discorrer sobre as reflexões éticas a respeito das práticas restaurativas como forma de se alcançar a justiça, e buscar, por meio dos objetivos específicos, apresentar as principais concepções de justiça e ética; entender a passagem da concepção de justiça retributiva para a concepção da justiça restaurativa; conceituar os conceitos norteadores da justiça restaurativa; interpretar eticamente os princípios e objetivos norteadores do Programa Municipal de Pacificação Restaurativa. O trabalho possui como objetivo propor, através de uma pesquisa bibliográfica qualitativa exploratória, reflexões éticas a respeito das práticas restaurativas como forma de se alcançar a justiça. Optou-se pelo delineamento exploratório por possuir o objetivo principal de apresentar um panorama do campo de pesquisa delimitado, de forma a apontar conceitos, áreas de atuação e pontos de interface da temática pesquisada. A pesquisa exploratória permitirá ao pesquisador aprimorar ideias e construir hipóteses a partir dos resultados obtidos. Aparentando ser o ideal para que o objetivo, de propor reflexões éticas a respeito das práticas restaurativas como forma de se alcançar a justiça, seja atingido. [resumo fornecido pelo autor]
Keywords: Ética; Justiça; Justiça restaurativa; Ethic; Justice; Restorative justice